Título Padrão - Nunes, Martha Suzana Cabral; Vilan Filho, Jayme Leiro (Informação em Pauta, 2023)
It presents a study on the characteristics of ENANCIB's GT3, related to scientific communication and collaboration. It starts from the following research question: how did evolve the GT3 research community about the scientific collaboration? The objective of this article is to show the evolution of some aspects of collaboration in GT3 from annual co-authorship indexes and to identify the authors with the highest participation in co-authorship and single authorship in GT3. It’s characterized as exploratory research with a quantitative approach using scientometric analysis to understand the co-authoring relationships observed throughout the existence of GT3 of the Associação Nacional de Pesquisa e Pós-Graduação em Ciência da Informação. To achieve this objective, a referential database of the Universidade de Brasília which contains bibliographic references of the GT3 productions from 2005 to 2019, was used as a main data source. These data were submitted to descriptive statistics application to observe how scientific collaboration between the authors takes place. It was concluded that the rates of multiple authorship increased in the years surveyed, while the rates of single authorship decreased, and some authors have a tendency to publish more in multiple or single authoring.